Electroencephalography in eating disorders - Jáuregui-Lobera I (Dove Medical Press, 2011)
Ignacio Jáuregui-Lobera1,21Behavioral Sciences Institute, 2Pablo de Olavide University, Seville, SpainAbstract: Clinical applications of electroencephalography (EEG) are used with different objectives, EEG being a noninvasive and painless procedure. In respect of eating disorders, in the 1950s a new line of study about the neurological bases of anorexia nervosa was started and has since been developed. The purpose of this review is to update the existing literature data on the main findings in respect of EEG in eating disorders by means of a search conducted in PubMed. Despite the fact that weight gain tends to normalize some brain dysfunctions assessed by means of EEG, the specific effect of gaining weight remains controversial. Different studies have reported that cortical dysfunctions can be found in patients with anorexia nervosa even after weight gain, whereas others have reported a normalization of EEG in respect of the initial reduced alpha/increased beta power in those patients with refeeding. Findings of studies that have analyzed the possible relationship between eating disorders and depression, based on sleep EEG disturbances, do not support the idea of eating disorders as a variant of depression or affective disorders. Some EEG findings are very consistent with previous neuroimaging results on patients with anorexia nervosa, reporting neural disturbances in response to stimuli that are relevant to the pathology (eg, stimuli like food exposure, different emotional situations, or body images).Keywords: electroencephalography, event-related potentials, sleep, depression, refeeding, weight gain